How public values theory can influence energy infrastructure planning: Exploring values articulation, time horizons, and substitutability through the Atlantic Coast pipeline. (February 2021) - Foley, Rider W.; Pollack, Catherine C.; Barrella, Elise; Wilkins, Rodney
Abstract: The transformation of energy infrastructure in the United States, specifically the expansion of the transportation network of natural gas pipelines, is garnering more public attention than ever before. Once built, energy infrastructure is long-lasting and exerts a strong influence on economic conditions, environmental integrity, and social behavior. Yet, clear, strategic energy plans are lacking and federal permitting focuses on economic factors. This research explores how public values theory can be operationalized to include noneconomic factors into planning for the transformation of energy infrastructure. However, there is a paucity of mechanisms to incorporate noneconomic values into decision-making processes related to energy infrastructure. Work remains to bridge theory and practice such that public values can shape planning and permitting processes. This research presents a case study on the Atlantic Coast Pipeline project, drawing upon survey data from 268 people and three workshops with 15 participants to inform the ongoing national debate on energy infrastructure. The survey analysis suggests three key determinants for pipeline infrastructure as illustrated by: i) models of scale (size and the proportional risk); ii) eminent domain (taking lands); and iii) protectionism ("Not In My BackYard, " or NIMBY). This research also showcases three alternative approaches on how to foster deliberative democratic processes with community members. This research extends the theoretical construct of public values theory by articulating mechanisms of action and assessing the efficacy of those mechanisms. Strategic planning for energy transitions and finding ways to reduce conflict may, in the long-term, minimize construction costs and address local concerns.